Semaglutide as a promising treatment for metabolic dysfunction‑associated steatotic liver disease - Zasadzińska, Maria; Borowski, Grzegorz (Journal of Medical Science, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is the most prevalent liver disorder globally, and if left untreated, it may progress to liver cirrhosis and even hepatocellular carcinoma. As of 2024, the European Association for the Study of the Liver Guidelines have recommended resmetirom as the only pharmacological treatment for adults with non-cirrhotic MASLD who have significant fibrosis (stage ≥2). However, lifestyle interventions and management of comorbidities, such as type 2 diabetes and obesity, remain the cornerstone of treatment. Glucagon-like peptide-1 receptor agonists, particularly semaglutide, have shown emerging promise in treating MASLD. Notably, the Phase III ESSENCE trial, presented in late 2024, demonstrated semaglutide's potential in improving liver fibrosis, confirmed through histological evaluation, marking a possible breakthrough for MASLD management. This review aims to synthesise current evidence on the efficacy of semaglutide in treating MASLD, highlighting its potential to fill a significant gap in the therapeutic options available for this growing global health concern.